2004
DOI: 10.2174/1568007043482570
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1 Receptors

Abstract: Among the seven classes of serotonin (5-hydroxytryptamine, 5-HT) receptors which have been identified to date, the 5-HT(1) class is comprised of five receptor types, with the 5-HT(1A), 5-HT(1B) and 5-HT(1D) characterized by a high affinity for 5-carboxamido-tryptamine, the 5-HT(1E) and 5-HT(1F) characterized by a low affinity for this synthetic agonist, and all five having a nanomolar affinity for the endogenous indolamine ligand. The genes encoding 5-HT(1) receptors have been cloned in both human and rodents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 0 publications
6
94
0
1
Order By: Relevance
“…In vitro distribution of 18 F-F13714 labeling in rat brain sections was consistent with the reported distribution of 5-HT 1A receptors in the hippocampus, dorsal raphe nucleus, and cortical areas (36). Interestingly, in vitro binding in the dorsal raphe nucleus was more pronounced for 18 F-F13714 than for 18 F-F15599 (34) and similar to 18 F-MPPF (37).…”
Section: Discussionsupporting
confidence: 85%
“…In vitro distribution of 18 F-F13714 labeling in rat brain sections was consistent with the reported distribution of 5-HT 1A receptors in the hippocampus, dorsal raphe nucleus, and cortical areas (36). Interestingly, in vitro binding in the dorsal raphe nucleus was more pronounced for 18 F-F13714 than for 18 F-F15599 (34) and similar to 18 F-MPPF (37).…”
Section: Discussionsupporting
confidence: 85%
“…This decrease is attributable to an increased level of extracellular 5-HT (Bel and Artigas, 1992;Yoshioka et al, 1995;Bonaventure et al, 2007) that leads to a greater activation of 5-HT 1A autoreceptors (Blier et al, 1984;Chaput et al, 1986;Le Poul et al, 1995;Haddjeri et al, 1998a). A full recovery is usually reported after about 2 or 3 weeks treatment with classical SSRIs (Chaput et al, 1986;de Montigny et al, 1990;Czachura and Rasmussen, 2000), a time course consistent with their delayed therapeutic Antidepressant-like profile of 5-HT 7 antagonism O Mnie-Filali et al effect (Blier and de Montigny, 1999;Lanfumey and Hamon, 2004). The recovery of the firing rate is believed to be due to a desensitization of the somatodendritic 5-HT 1A autoreceptors of 5-HT neurons in DRN (Blier and de Montigny, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, a series of neuroadaptive changes must first occur for this to happen, and these changes are thought to underlie the prolonged therapeutic latency of these drugs (Blier and de Montigny, 1999;Duman et al, 2001;Nestler et al, 2002). Examples of the above mentioned changes include a progressive desensitization of raphe 5-HT 1A autoreceptors and a stimulation of the cell proliferation in the dentate gyrus (DG) of the hippocampus following long-term treatment with SSRIs, with a time course consistent with their delayed AD effects (Blier and de Montigny, 1999;Hensler, 2002;Santarelli et al, 2003;CastrĂ©n, 2004;Lanfumey and Hamon, 2004;Faure et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding 5-HT, one possible way out would be to target 5-HT receptors involved in the regulation of satiety that are predominantly expressed in the brain. The 5-HT1B receptor is a less likely target, as this receptor is also located on vascular tissues [343], hence causing potentially vascular side effects. Based on experimental and human studies, the 5-HT2C receptor has been identified as a possible target for anti-obesity drugs [338].…”
Section: Serotonin and The Pharmacotherapy Of Obesitymentioning
confidence: 99%